2014
DOI: 10.1007/978-1-4939-1384-8_10
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Random Search Methods

Abstract: This chapter provides a brief review of random search methods for simulation optimization. We start by describing the structure of random search when system performance is estimated via simulation. Next, we discuss methods for solving simulation optimization problems with discrete decision variables and one (stochastic) performance measure, with emphasis on simulated annealing. Finally, we expand our scope to address simulation optimization problems with continuous decision variables and/or multiple (stochasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 83 publications
(97 reference statements)
0
18
0
Order By: Relevance
“…Nonetheless, Bergstra and Bengio (2012) showed that it is (at least) as good as more advanced versions of random search. More details on these algorithms can be found in Solis and Wets (1981) and Andradóttir (2015).…”
Section: Hyperparameters Selectionmentioning
confidence: 99%
“…Nonetheless, Bergstra and Bengio (2012) showed that it is (at least) as good as more advanced versions of random search. More details on these algorithms can be found in Solis and Wets (1981) and Andradóttir (2015).…”
Section: Hyperparameters Selectionmentioning
confidence: 99%
“…-Random search randomly picks combinations from all possible ones. It may not find a decent combination but is widely adopted in industry for the high-efficiency [1]. -Bayesian optimization uses a Gaussian process to minimize the loss function in order to maximize performance [10].…”
Section: Overall Comparisonmentioning
confidence: 99%
“…Random Search, which is developed based on grid research, set up a grid of arXiv:1907.13359v1 [cs.LG] 31 Jul 2019 hyper-parameter values and selects random combinations to train the algorithm [2]. Random search method oversteps some disadvantages of grid search such as time-consuming but meanwhile brings a major disadvantage which cannot converge to the global optimum [1]. The randomly selected hyper-parameter combinations cannot guarantee a steady and competitive result.…”
Section: Introductionmentioning
confidence: 99%
“…An incomplete list of recent examples includes model reference adaptive search (Hu et al 2007), adaptive search with resampling (Andradóttir and Prudius 2010), gradient-based adaptive stochastic search (Zhou and Bhatnagar 2018), and single observation search (Kiatsupaibul et al 2018). We refer to Andradóttir (2015) and Zabinsky (2015) for reviews of random search methods.…”
Section: Related Workmentioning
confidence: 99%